Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4049/jimmunol.1002747
|View full text |Cite
|
Sign up to set email alerts
|

Forced Expression of HLA-DM at the Surface of Dendritic Cells Increases Loading of Synthetic Peptides on MHC Class II Molecules and Modulates T Cell Responses

Abstract: Adoptive transfer of autologous dendritic cells (DCs) loaded with tumor-associated CD4 and CD8 T cell epitopes represents a promising avenue for the immunotherapy of cancer. In an effort to increase the loading of therapeutic synthetic peptides on MHC II molecules, we used a mutant of HLA-DM (DMY) devoid of its lysosomal sorting motif and that accumulates at the cell surface. Transfection of DMY into HLA-DR+ cells resulted in increased loading of the exogenously supplied HA307–318 peptide, as well as increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…M1 macrophages also overexpressed HLA‐DM compared with M1 microglia. HLA‐DM plays a role in MHC peptide loading and has been shown to bias T‐cell differentiation towards the Th1 lineage (Pezeshki et al,2011). Our data suggest that regardless of polarization state, macrophages may play a more significant role than microglia in antigen presentation, with M1 macrophages more likely to bias Th1 responses.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages also overexpressed HLA‐DM compared with M1 microglia. HLA‐DM plays a role in MHC peptide loading and has been shown to bias T‐cell differentiation towards the Th1 lineage (Pezeshki et al,2011). Our data suggest that regardless of polarization state, macrophages may play a more significant role than microglia in antigen presentation, with M1 macrophages more likely to bias Th1 responses.…”
Section: Discussionmentioning
confidence: 99%
“…DM nevertheless is also found in all endocytic compartments where it is supposed to contribute to a greater or lower extent to peptide editing, and for some cell types even at the cell surface 63 . Although DM activity at the surface is usually ignored, it has been shown that overexpression of a mutant which is retained at the cell surface can indeed favor extracellular peptide biding 64 . Similarly, our recent description of a DM allotype with a considerably higher activity at neutral pH may have a significant impact on peptide editing at the cell surface 9 …”
Section: Peptide Editing By Hla‐dmmentioning
confidence: 99%
“…However, the Neefjes laboratory demonstrated at the cellular level by Fö rsters resonance energy transfer (FRET) that DM-DR interaction is pH-independent [115]. Moreover, Thibodeau et al have also shown that DM indeed can catalyse peptide-exchange on the cell surface modulating T-cell responses [116]. It is worth noting that those studies were based on overexpression of the different MHC proteins under consideration and the physiological barriers to interaction may be overcome at high expression levels.…”
Section: Biochemical and Structural Insights Into The Function Of Hla-dmmentioning
confidence: 99%